2005
DOI: 10.1128/jvi.79.8.5000-5005.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Currently Circulating Human Immunodeficiency Virus Type 1 Clade B Viruses Fail To Prime Cytotoxic T-Lymphocyte Responses against an Otherwise Immunodominant HLA-A2-Restricted Epitope: Implications for Vaccine Design

Abstract: Human immunodeficiency virus type 1 (HIV-1) mutates to escape immune selection pressure, but there is little evidence of selection mediated through HLA-A2, the dominant class I allele in persons infected with clade B virus. Moreover, HLA-A2-restricted responses are largely absent in the acute phase of infection as the viral load is being reduced, suggesting that circulating viruses may lack immunodominant epitopes targeted through HLA-A2. Here we demonstrate an A2-restricted epitope within Vpr (Vpr 59-67 ) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…A different pattern of changing epitopic usage over time is illustrated by responses to the immunodominant HLA-A2-restricted Gag 77-85 ( 77 SLYNTV ATL 85 [SL9]) epitope in p17 Gag. SL9 is recognized by the majority of chronically infected individuals but not by most acutely infected individuals (4,10,16,18,21,24,37). This temporal relationship for CTL recognition of virus proteins/ epitopes is also supported by observations that the HIV-1-Nef protein is recognized before other proteins (2,5,9,28) and, in mouse models, by constantly evolving CTL immunodominance (7,(42)(43)(44).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…A different pattern of changing epitopic usage over time is illustrated by responses to the immunodominant HLA-A2-restricted Gag 77-85 ( 77 SLYNTV ATL 85 [SL9]) epitope in p17 Gag. SL9 is recognized by the majority of chronically infected individuals but not by most acutely infected individuals (4,10,16,18,21,24,37). This temporal relationship for CTL recognition of virus proteins/ epitopes is also supported by observations that the HIV-1-Nef protein is recognized before other proteins (2,5,9,28) and, in mouse models, by constantly evolving CTL immunodominance (7,(42)(43)(44).…”
supporting
confidence: 52%
“…Using the intracellular cytokine flow cytometry (ICS) assay (23,24), only 3 of 20 patients had a detectable CTL response measured by the production of interferon gamma (IFN-␥) against the SL9 epitope. Prior studies have repeatedly shown responses to the SL9 epitope in the majority of chronically infected, antiretroviral-untreated subjects (4,18,21,22,37), although these responses were not always immunodominant (8).…”
mentioning
confidence: 99%
“…Although reduced infection risk with possession of the HLA-A2 supertype was reported for two Nairobi cohorts (17), HLA-A2-restricted CTL responses to clade B virus infection do not appear to suppress virus effectively in infected individuals (18 -20). This has led to the suggestion that useful HLA-A2-restricted epitopes in circulating clade B viruses may have been lost because the clade B epidemic is historically older than the clade C epidemic and HLA-A2 is more prevalent in the West than in Africa (19,20). Loss of epitopes restricted by MHC alleles with high frequencies was also supported by studies in HIV-1 clade C-infected cohorts (21,22) and in SIV-infected macaques (23).…”
mentioning
confidence: 67%
“…HLA typing was possible for 280 of these samples, of which 121 were HLA-A2 ϩ . OLP21 (PRTLNAWVKVVEEKAP, p24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) was recognized by 24 subjects, with most of this reactivity (14 of 24) likely directed against the HLA-B*1503-restricted VKV VEEKAF epitope frequently seen in HLA-B*1503-expressing subjects (21). Reactivity to the nonameric TV9 peptide was confirmed in one of two HLA-A2 ϩ HLA-B*1503 Ϫ samples tested that reacted to OLP21 (L8 47, 500 sfc/10 6 PBMCs; Fig.…”
Section: Tv9 Reactivity In Hiv-1-infected Subjectsmentioning
confidence: 99%
“…In contrast, A*02 and B*07 were associated with higher VRC (0.948 versus 0.816 for A*02 and 0.987 versus 0.831, q ϭ 0.175, respectively [ Table 1]). The fact that these alleles are both common in the U.S. population (A*02 frequency, 28.3% for Caucasians and 18.7% for African Americans; B*07 frequency, 11.3% for Caucasians and 9.8% for African Americans) (12) suggests the possibility that these are not actively increasing VRC but rather that the virus may have become most adapted to these populations, rendering them neutral in comparison to a large group of less-frequent HLA alleles, which may still be impacting viral load (1,20,29).…”
Section: Resultsmentioning
confidence: 99%